Effects of Chemical Reaction and Joule Heating on MHD Generalized Couette Flow between Two Parallel Vertical Porous Plates with Induced Magnetic Field and Newtonian Heating/Cooling - Jumanne Mng’ang’a (International Journal of Mathematics and Mathematical Sciences)
In this article, the effects of chemical reaction and Joule heating on MHD generalized Couette flow between two vertical porous plates with induced magnetic field and Newtonian heating/cooling have been investigated. The mathematical model used for the MHD generalized Couette flow takes into account the effect of viscous dissipation. The system of nonlinear partial differential equations governing the flow was solved numerically using the finite difference method. The resulting numerical schemes are simulated in MATLAB to obtain the profiles of the flow variables such as velocity, induced magnetic field, temperature, and concentration profiles graphically. Also, the effects of the flow parameters on the skin-friction coefficient, Nusselt number, and Sherwood number are obtained and discussed numerically through tabular forms. The findings show that an increase in the chemical reaction parameter leads to a decrease in the concentration profiles. Also, increase in the Joule heating parameter and heat generation parameter leads to an increase in the temperature profiles. Induced magnetic field profiles increase with an increase in Reynold’s number. The findings of this study are important due to its application in developing a variety of chemical technologies, including polymer manufacturing, MHD pumps, food processing, chemical catalytic reactors, astronomy, MHD flow meters, and lubrication.